Identitas Nasional Indonesia dalam Bingkai Kebangsaan: Analisis Fiqh Siyasah - Ahmad Muhamad Mustain Nasoha; Nida Nur Hidayati; Latifah Rahmadani Oktaviana; Farah Aghnia Fauzia; Mutiara Dwi Rachmawati (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This research discusses Indonesia's national identity in the framework of citizenship using the perspective of Fiqh Siyasah. The background of this research is the importance of integrating Islamic values in strengthening a pluralistic national identity in the midst of the social, political, and cultural dynamics of modern society. The purpose of this study is to examine the relationship between the concept of modern citizenship and the principles of Fiqh Siyasah and its implications for strengthening national identity. The research method used is a qualitative study with a literature analysis approach, which allows the author to explore various classical and contemporary sources related to the concept of citizenship in Islam and its application in Indonesia. The results of the study show that the values of Fiqh Siyasah, such as justice, benefit, and unity, can be a moral and ethical foundation in strengthening Indonesia's inclusive, democratic, and equitable national identity. In addition, its implementation can strengthen the sense of responsibility of citizens in maintaining the stability of the nation. The conclusion of the study emphasizes the importance of collaboration between Islamic thought and national principles to build a sustainable national identity that is adaptive to the changing times.